Application of the magnetotelluric method in geothermal exploration in Jianshi county, Hubei province, China - Peng Simeng; Xie Xingbing; Zhang Lianqun; Rao Song; Zhou Lei; Lu Chuyang; Li Yuxi (Discover Geoscience)
Abstract Geothermal resource is a kind of renewable green and clean energy stored in the earth’s interior. Under the impetus of the global energy revolution and the goal of “double-carbon”, the development and utilization of geothermal energy has become an important strategy for the energy development of all countries in the world. The Magnetotelluric (MT) sounding method, which is not shielded by high-resistance layers and provides high resolution for low-resistance layers, has unique advantages in revealing geothermal system structures, delineating hydrothermal geoelectric structures, and assessing the development potential of geothermal regions. Based on an MT profile in Maotian Township, Jianshi County, this paper processed data from 51 broadband MT measurement points using Fourier transform, Robust estimation, and impedance tensor decomposition techniques. After a detailed analysis of the dimensional characteristics and electrical axes, a 2D electrical structure model from the surface to a depth of 9 km was obtained via topography-based 2D inversion. The fault distribution was confirmed, and the potential geothermal resource areas were inferred based on geological information. The MT-sounding survey confirmed the favorable geothermal resource storage range in the study area and demonstrated the advantages of MT in geothermal exploration, with important practical value for investigating the underground electrical structure and geothermal resource distribution.